The critical lacuna between new contextually juxtaposed and freestyle buildings in historic settings - Riza, Müge; Doratli, Naciye (Locke Science Publishing Company Inc. customercare@lockescience.com, 2015)
New building design in historic settings is not a new source of debate. Indeed there has always been a fear that the sense of place and identity of a historic area might be ignored or negatively affected if new buildings are added. Thus, there has been wide-ranging discussion regarding how to integrate new buildings into existing contexts, and the harmonious integration of buildings has been a key concern of many scholars and institutions. However, analysis of different examples of new buildings in historic settings has revealed a need for further study of the varying impacts of new buildings on the sense of place of historic areas when they are integrated in a contextually juxtaposed versus non-contextual or freestyle way. Thus, the major aim of this paper is to question the distinctiveness of the contextual juxtaposition and non-contextual freestyle design approaches. Based on a detailed review of the literature, the paper first outlines the current discussions and arguments surrounding the integration of new buildings into historic settings and how they contribute to the physical character of historic settings. It then presents and evaluates different design approaches to new building design in historic settings using four diverse examples from two countries. Finally, the paper concludes with a discussion of the subtle nuances between the contextual juxtaposition and non-contextual/freestyle design approaches with regard to the sense of place. © Copyright 2015, Locke Science Publishing Company, Inc. Chicago, IL, USA All Rights Reserved .
Keywords: architectural design; critical analysis; historic building; historical record; literature review; sense of place; Lacuna